ANALYTICAL HIERARCHY PROCCESS (AHP) PADA SISTEM INFORMASI GEOGRAFIS BERBASIS WEB UNTUK PERENCANAAN PENEMPATAN TOKO MODERN (STUDI KASUS DI KOTA JAMBI) - Lailyn Puad (JURNAL AKADEMIKA)
The rapid growth rate of modern store in the town of Jambi brings a wide range of positive impacts to the economy of the community, but also gives a negative impact for some parties or industries. Furthermore, in order to make decisions of modern store location assignment planning, it has to be more observed. An Analytical Hierarchy Process (AHP) method is a method that can be used in the process of taking decisions to determine the location of the modern store placement. The decision makers will provide some criteria or rules in determining the location as well as providing values for each criterion. From the AHP calculation based on the great degree criteria will be gained AHP‘s values for each alternative location. That AHP‘s values are used by the system to determine the most optimal location of candidate locations. With the integration of the AHP method into a geographic information system (GIS), there will be a system that can provide detailed information as well as visualization into the digital map of Google Maps that can be used as a reference for decision-makers, especially in searching for a new optimal branch location.